Minimum Wages and Excessive Effort Supply - Matthias Kräkel; Anja Schöttner (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
It is well-known that, in static models, minimum wages generate positive worker rents and, consequently, ine?ciently low effort. We show that this result does not necessarily extend to a dynamic context. The reason is that, in repeated employment relationships, ?rms may exploit workers' future rents to induce excessively high effort.
Keywords: D82; D86; J33; 330; bonuses; limited liability; minimum wages; Mindestlohn; Leistungsmotivation; Arbeitsvertrag; Vertragstheorie; Theorie